The Efficacy and Safety of On-demand Tramadol and Paroxetine Use in Treatment of Life Long Premature Ejaculation: A Randomized Double-blind Placebo-controlled Clinical Trial - A Hamidi-Madani; R Motiee; G Mokhtari; H Nasseh; S Esmaeili; E Kazemnezhad (JRI, 2018)
Background: Several medical therapies have been proposed for the treatment of premature ejaculation (PE). Paroxetine and tramadol were both reported to be effective in treatment of PE. In this study, the therapeutic effects of tramadol, paroxetine and placebo were compared in treatment of primary PE. Methods: In this randomized, double-blind, placebo-controlled clinical trial, 150 patients were divided into 3 groups. One group was treated with tramadol 50 mg on- demand, the other group took paroxetine 20 mg on-demand and the third group was treated with placebo. Before starting treatment and after 12 weeks, patients were asked to measure their average intravaginal ejaculation latency time (IELT) and fill the PEP (Premature Ejaculation Profile) questionnaire. Results: At the end of the 12th week, the mean IELT and average of PEP scores improved in all 3 groups. The increase in tramadol group was significantly higher than the paroxetine and placebo groups (p<0.0001). There were no significant differences in terms of side effects between the 3 groups. Conclusion: The results showed that despite an increase in mean IELT and PEP scores in all 3 groups, the rate of improvement in tramadol group was significantly more than the others. Thus, tramadol may be considered as an appropriate alternative therapeutic option for lifelong PE.